Synthesis of esters of diaminotruxillic bis-amino acids by Pd-mediated photocycloaddition of analogs of the Kaede protein chromophore - Urriolabeitia, Esteban P.; Sánchez, Pablo; Pop, Alexandra; Silvestru, Cristian; Laga, Eduardo; Jiménez, Ana I.; Cativiela, Carlos (Beilstein Journal of Organic Chemistry, 2020)
The stereoselective synthesis of truxillic bis-amino esters from polyfunctional oxazolones is reported. The reaction of 4-((Z)-arylidene)-2-(E)-styryl-5(4H)-oxazolones 2 with Pd(OAc)2 resulted in ortho-palladation and the formation of a dinuclear open-book complexes 3 with carboxylate bridges, where the Pd atom is C^N bonded to the oxazolone. In 3 the two exocyclic C=C bonds of the oxazolone are in a face-to-face arrangement, which is optimal for their [2 + 2] photocycloaddition. Irradiation of dimers 3 in CH2Cl2 solution with blue light (465 nm) promoted the chemo- and stereoselective [2 + 2] photocycloaddition of the exocyclic C=C bonds and the formation of cyclobutane-containing ortho-palladated complexes 4. Treatment of 4 with CO in a MeOH/NCMe mixture promoted the methoxycarbonylation of the palladated carbon and the release of the corresponding ortho-functionalized 1,3-diaminotruxillic bis-amino esters 5 as single isomers.
Keywords: amino acids; C–H activation; Kaede protein; oxazolones; photocycloaddition